Mirogabalin 15 mg Twice Daily for Reduction of Average Daily Pain Score in Neuropathic Pain: Systematic Review and Meta-analysis of Randomized Controlled Trials - Andra Danika; Paulus Alexander Supit (International Medical Journal Corp. Ltd, 2025)
Background: Neuropathic pain is a chronic condition that significantly impairs quality of life, causing sleep disturbance, depression, and functional disability. Standard first-line treatments such as pregabalin and gabapentin are frequently limited by insufficient efficacy or poor tolerability. Mirogabalin is a novel α2δ ligand with slower dissociation from the α2δ-1 subunit of voltage-gated calcium channels, potentially offering sustained analgesia with improved tolerability. Objective: To systematically review and meta-analyze randomized controlled trials (RCTs) assessing the efficacy and safety of mirogabalin 15 mg twice daily compared with placebo in adult patients with neuropathic pain. Methods: This systematic review and meta-analysis followed PRISMA 2020 guidelines. PubMed, Embase, and Cochrane CENTRAL were searched from database through September 2025 for double-blind, placebo-controlled RCTs. The primary outcome was mean change from baseline in average daily pain score (ADPS). Secondary outcomes included ≥30% pain responder rate and treatment-emergent adverse events. Random-effects meta-analysis was performed to calculate pooled mean difference (MD) and risk ratio (RR) with 95% confidence intervals (CIs). Risk of bias was assessed using Cochrane RoB 2.0. Results: Four RCTs with a total of 1,819 participants were included. Mirogabalin significantly reduced ADPS compared with placebo (pooled MD −0.57, 95% CI −0.73 to −0.41; p < 0.00001; I² = 0%). Pooled analysis of dichotomous outcomes demonstrated a significantly greater likelihood of achieving ≥30% pain reduction with mirogabalin (RR 1.26, 95% CI 1.11–1.44; p < 0.01). Most studies had low risk of bias. The most common adverse events were somnolence and dizziness, which were generally mild to moderate. Conclusions: Mirogabalin 15 mg twice daily significantly improves pain outcomes compared with placebo, both in mean ADPS reduction and responder rate, and is generally well tolerated. Although the mean pain reduction is modest, the improved responder rate suggests that a clinically meaningful proportion of patients may benefit. Further research should explore long-term efficacy, optimal dosing, and predictors of response.